2020
DOI: 10.1101/2020.06.05.136077
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dopaminergic Modulation of Working Memory and Cognitive Flexibility in a Zebrafish Model of Aging-Related Cognitive Decline

Abstract: Part of the natural aging process is a decline in memory and executive function, even in the absence of disease. The dopaminergic system has been implicated in age associated alterations in cognitive flexibility and working memory. Here we examine the relationship between cognitive performance and dopamine function of young-adult and aging zebrafish (Danio rerio). We reveal an age-related decrease in working memory and cognitive flexibility when faced with a negative feedback loop for informing search strategi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 99 publications
1
1
0
Order By: Relevance
“…Poorer habituation in zebrafish treated by 1 mg/L GBR 12909, seen in the present study, strikingly recapitulates reduced spatial working memory reported in the DAT knockout mice (Li et al, 2010). Somewhat similar working memory decline is also observed in adult zebrafish with reduced DAT expression following a dopamine D1/D5 receptor agonist SKF-38393 treatment at young ages (Cleal et al, 2021a). Natural rise of zebrafish locomotion in the habituation test was reduced by GBR 12909 at all doses used here (Supplemental Table S1), paralleling similar effects of a relatively novel DAT inhibitor, CE-123, thus attenuating an alcohol-induced hyperactivity in rats (Gibula-Tarlowska et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…Poorer habituation in zebrafish treated by 1 mg/L GBR 12909, seen in the present study, strikingly recapitulates reduced spatial working memory reported in the DAT knockout mice (Li et al, 2010). Somewhat similar working memory decline is also observed in adult zebrafish with reduced DAT expression following a dopamine D1/D5 receptor agonist SKF-38393 treatment at young ages (Cleal et al, 2021a). Natural rise of zebrafish locomotion in the habituation test was reduced by GBR 12909 at all doses used here (Supplemental Table S1), paralleling similar effects of a relatively novel DAT inhibitor, CE-123, thus attenuating an alcohol-induced hyperactivity in rats (Gibula-Tarlowska et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…The FMP Y-maze has shown that different species such as zebrafish, rats and humans adopt alternations (rlrl or lrlr) as the main strategy to escape from the maze (Cleal et al, 2020). In zebrafish, during 1 hour of testing, the animals tend to increase their alternations up to 40 minutes (peak of activity) which then reduces due to the energy demanding nature of the task (Cleal et al, 2021;Cleal et al, 2020). Researchers have concluded the percentage of alternations during the test is correlated with overall working memory, with changes in behavior over the course of the task reflective of behavioral adaptability and cognitive flexibility (Cleal et al 2020).…”
Section: Discussionmentioning
confidence: 99%